Whole transcriptome profiling of successful immune response to Vibrio infections in the oyster Crassostrea gigas by digital gene expression analysis. - Julien de Lorgeril; Reda Zenagui; Rafael D Rosa; David Piquemal; Evelyne Bachère (PLoS ONE, 2011)
The cultivated Pacific oyster Crassostrea gigas has suffered for decades large scale summer mortality phenomenon resulting from the interaction between the environment parameters, the oyster physiological and/or genetic status and the presence of pathogenic microorganisms including Vibrio species. To obtain a general picture of the molecular mechanisms implicated in C. gigas immune responsiveness to circumvent Vibrio infections, we have developed the first deep sequencing study of the transcriptome of hemocytes, the immunocompetent cells. Using Digital Gene Expression (DGE), we generated a transcript catalog of up-regulated genes from oysters surviving infection with virulent Vibrio strains (Vibrio splendidus LGP32 and V. aestuarianus LPi 02/41) compared to an avirulent one, V. tasmaniensis LMG 20012(T). For that an original experimental infection protocol was developed in which only animals that were able to survive infections were considered for the DGE approach. We report the identification of cellular and immune functions that characterize the oyster capability to survive pathogenic Vibrio infections. Functional annotations highlight genes related to signal transduction of immune response, cell adhesion and communication as well as cellular processes and defence mechanisms of phagocytosis, actin cytosqueleton reorganization, cell trafficking and autophagy, but also antioxidant and anti-apoptotic reactions. In addition, quantitative PCR analysis reveals the first identification of pathogen-specific signatures in oyster gene regulation, which opens the way for in depth molecular studies of oyster-pathogen interaction and pathogenesis. This work is a prerequisite for the identification of those physiological traits controlling oyster capacity to survive a Vibrio infection and, subsequently, for a better understanding of the phenomenon of summer mortality.